EFEKTIFITAS TEKNIK MENERAN TERHADAP KEJADIAN RUPTURE PERINEUM PADA IBU BERSALIN - Desi Ernita Amru (Lembaga Pengembangan Kinerja Dosen, 2022)
Mechanical menerant is an influence on the incidence of perineal rupture in normal delivery that causes postpartum hemorrhage. Bleeding is the main cause of maternal death in Indonesia. The results of a survey conducted that the incidence of perineal rupture was caused by a pressing technique error. This study aims to determine the effectiveness of the pressing technique on the incidence of perineal rupture at the Batam City OW Clinic in 2020. This type of research is an analytical survey. The data collection technique used is primary data using observation sheets. The sample in this study were all normal mothers who gave birth at the Batam City OW Clinic, totaling 47 people. Based on the results of research conducted from 47 respondents, there were 15 respondents (31.9%) who pushed correctly, it was found that 13 respondents (72.2%) had no perineal rupture. while 32 respondents (68.1%) who said incorrectly, 27 respondents (93.1%) experienced perineal rupture after statistical tests (chi-square test) obtained a P-value of 0.000. This means that Ho is rejected and Ha is accepted, so it can be concluded that the pushing technique is really effective against the incidence of perineal tears in maternity mothers.